PERAN SMART FISHERIES VILLAGE DALAM MENINGKATKAN EKONOMI LOKAL MELALUI WISATA EDUKASI DAN KULINER : STUDI KASUS KAMPUNG NILA KAWALI - Rahayu, Sinta Puspa; Saputra, Ginanjar Wira; Sahadi, Sahadi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to analyses the role of Smart Fisheries Village in encouraging community empowerment and strengthening the village economy through fisheries-based business diversification. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation studies, analyses using a triangulation approach for data validity. The results of the study indicate that the implementation of the Smart Fisheries Village concept in Kampung Nila is able to create a new economic value chain through the integration of fish farming, educational tourism, and culinary. The resulting impacts include increased community income, the birth of new micro-enterprises, and increased employment in the tourism services sector and fishery product processing MSMEs. The existence of educational and culinary tourism based on tilapia has succeeded in attracting the attention of students, university students, and tourists, thereby expanding the local market. The study also found several obstacles such as limited infrastructure, low technological literacy, and weak branding strategies in the area. The researchers concluded that Smart Fisheries Village plays a significant role in improving the local economy and community empowerment through an integrative approach between the fisheries, education, and culinary sectors. Its innovation lies in the link between educational and culinary tourism with the economic sustainability of the fishing village. This research contributes to the development of the Smart Fisheries Village concept as well as policy recommendations to strengthen branding strategies, human resource capacity building, and marketing partnerships to create a local fisheries economy.